Pelatihan Penggunaan Software Geogebra Bagi Guru MTSN 2 Bengkulu Tengah - Siska, Jumiati; Selviani, Diah; Asnawati, Asnawati; Saputra, Fallela Rohma; Lestari, Monica Indah (Universitas Dehasen Bengkulu, 2024)
The proposed Community Service (PKM) is